ZAKAT VS PAJAK: STUDI PERBANDINGAN DI BEBERAPA NEGARA MUSLIM (UIN Sunan Kudus, 2014)
This article aims to reveal the relationship between zakat and taxesin some Muslim countries. In the early days of Islam, an obligationimposed on the Muslim zakat was collected only managed by the State.However, over the time, and increased state spending needs, then inaddition to zakat, Muslims are also burdened with dharibah (tax) tocover the budget deficit. This article is produced from the literaturefrom a variety of sources with inductive method. Results of the studyfound that the relationship between zakat and taxation in Saudi Arabia,Malaysia and Indonesia had a significant difference. Saudi Arabiaenforces a single obligation means Muslim citizens who already payzakat is not obligated to pay taxes. When Malaysia imposed a charityas a tax deduction if the charity paid out in the institution’s officialcharity. While Indonesia imposed a system of tax deduction in thesense, zakat which has been paid residents can reduce taxable income.